ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR NONMIGAS INDONESIA KE AMERIKA SERIKAT - Editiawarman, Editiawarman; idris, idris (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
In this study the study of Analysis of factors affecting IndonesianNon-oil and gas exports to America and the data used in this study isquarterly time series data from 2007Q1-2018Q. The model used in thisstudy is the Error Correction Model / ECM. Data sourced from the WorldBank and the Ministry of Trade. The results of this study indicate that (1)the estimated economy of the United States in the long term and short termhas a significant positive relationship to Indonesia's non-oil and gas exports to the United States (2) a significant negative effect on Indonesia's non-oil and gas exports to the United States (3) Foreign direct investment or investment foreign direct in the long run, has a significant positive and in the short term does not have a significant and positive influence on non-oil and gas exports Indonesia to the United States.